Selection Strategy for Yield Improvement of Chickpea Genotypes (Cicer arietinum L.) - , Kushalam Bharath, G. Roopa Lavanya (Archives of Current Research International, 2024)
An investigation was undertaken to assess the genetic variability parameters, correlation and path analysis in 25 chickpea genotypes for 12 quantitative traits during the Rabi season of 2022-23 in a Randomized Block Design with three replications. Analysis of variance indicated high significant differences among the genotypes for all the traits. Considerable variability existed in the genotypes for all the characters studied. The study found that CG23, CG159, and CG199 were the most superior genotypes for grain yield per plant among 25 chickpea genotypes. High PCV, GCV, heritability and genetic advance as percent of mean were recorded for test weight and biological yield. Grain yield per plant showed positive significant association with number of pods, days to maturity, days to 50% pod initiation and number of primary branches. High and positive direct effect of grain yield per plant at both phenotypic and genotypic levels were depicted by harvest index. These characters may be taken into consideration for selection of quantitative characters for crop improvement.